Synthesis of quinoline derivatives as diabetic II inhibitors and molecular docking studies - Taha, Muhammad; Sultan, Sadia; Imran, Syahrul; Rahim, Fazal; Zaman, Khalid; Wadood, Abdul; Ur Rehman, Ashfaq; Uddin, Nizam; Mohammed Khan, Khalid (Bioorganic & medicinal chemistry, 2019)
[Display omitted] In searchof the potenttherapeutic agent as an α-glucosidase inhibitor, we have synthesized twenty-five analogs (1–25) of quinoline-based Schiff bases as an inhibitoragainst α-glucosidase enzyme under positive control acarbose (IC50 = 38.45 ± 0.80 µM). From the activity profile it was foundthat analogs 1, 2, 3, 4, 11, 12 and 20with IC50values 12.40 ± 0.40, 9.40 ± 0.30, 14.10 ± 0.40, 6.20 ± 0.30, 14.40 ± 0.40, 7.40 ± 0.20 and 13.20 ± 0.40 µMrespectively showed most potent inhibition among the series even than standard drug acarbose (IC50 = 38.45 ± 0.80 µM). Here in the present study analog 4 (IC50 = 6.20 ± 0.30 µM) was found with many folds better α-glucosidase inhibitory activity than the reference drug. Eight analogs like 5, 7, 8, 16, 17, 22, 24 and 25 among the whole series displayed less than 50% inhibition. The substituents effects on phenyl ring thereby superficially established through SAR study. Binding interactions of analogs and the active site of ligands proteins were confirmed through molecular docking study. Spectroscopic techniques like 1H NMR, 13C NMR and ESIMS were used for characterization.